Penerapan Metode AHP untuk Sistem Pendukung Keputusan Pemilihan Siswa Teladan - Puspita, Ari; Hilda Amalia; Ida Faridah; Seni Kurniasari; Yuyun Yuningsih (Infotek: Jurnal Informatika dan Teknologi, 2025)
Students are an important element in education who are expected to become quality individuals. The selection of exemplary students is important to do, this aims to motivate students to excel, but a system that only relies on academic grades can hinder non-academic development. Therefore, non-academic aspects such as morals and extracurricular activities are also included in the assessment. Decision Support Systems (DSS) help analyze situations with criteria that are not always clear, using the Analytical Hierarchy Process (AHP) method to organize complex problems. This study developed a DSS for selecting exemplary students at SMP Muhammadiyah Kawali with four criteria: attendance, discipline, achievement, and extracurricular. The results showed that exemplary students with the highest weighted scores scored 0.1920. The resulting DSS was able to select exemplary students more objectively and transparently based on existing criteria, namely discipline, attendance, achievement and extracurricular activities. With the implementation of this system, it is able to increase objectivity and fairness in selecting exemplary students and motivate students to achieve better